2009
DOI: 10.1007/s10899-009-9124-1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Problem Gambling to Criminal Behavior in a Sample of Canadian Male Federal Offenders

Abstract: This article examines the prevalence of moderate and severe problem gambling in a sample of 254 incarcerated Canadian male federal offenders (completion rate of 39.0%). The prevalence of disordered gambling was measured using the PGSI, DSM-IV-TR, and SOGS that yielded estimates of 9.4%, 6.3%, and 13.0%, respectively. Severe problem gamblers were significantly more likely to have committed income producing offences, but were neither more nor less likely than other offenders to have committed violent offences. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
93
3
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 19 publications
19
93
3
5
Order By: Relevance
“…Similar prevalence numbers have been found in more recent studies (May-Chahal, Wilson, Humphreys, & Anderson, 2012;Turner, Preston, McAvoy, & Gillam, 2013;Turner, Preston, Saunders, & McAvoy, 2009). Among participants recruited from several provincial and federal correctional institutions in Ontario, Turner et al (2009Turner et al ( , 2013 report that slightly less than a quarter of those surveyed had either a moderate or severe gambling problem and, in particular, 9% had a severe gambling problem . The rate of moderate and severe problem gambling (PG) in these studies is about 10 times that of the general population (Williams, Volberg, & Stevens, 2012).…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar prevalence numbers have been found in more recent studies (May-Chahal, Wilson, Humphreys, & Anderson, 2012;Turner, Preston, McAvoy, & Gillam, 2013;Turner, Preston, Saunders, & McAvoy, 2009). Among participants recruited from several provincial and federal correctional institutions in Ontario, Turner et al (2009Turner et al ( , 2013 report that slightly less than a quarter of those surveyed had either a moderate or severe gambling problem and, in particular, 9% had a severe gambling problem . The rate of moderate and severe problem gambling (PG) in these studies is about 10 times that of the general population (Williams, Volberg, & Stevens, 2012).…”
Section: Introductionsupporting
confidence: 91%
“…Our review uncovered a number of programs within the criminal justice system that have been implemented to help individuals with gambling problems. As noted in the Introduction, previous studies have shown that many people in correctional settings have a severe gambling problem (e.g., May-Chahal et al, 2012;Perrone et al, 2013;Turner et al, 2009Turner et al, , 2013Williams et al, 2005). Although several case studies involved programs that offered services to this population, currently none of the programs examined are widely available to people who are incarcerated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Problem gambling has been linked to a variety of harmful mental and physical health consequences, as well as a wide variety of problems such as high criminality and homelessness (Blaszczynski and Silove 1996;Shaffer et al 2004;Stein et al 2012;Turner et al 2009). These consequences make PG an important public health problem, especially for more vulnerable populations (Gainsbury et al 2014;Korn and Shaffer 1999;Papineau 2010;Shaffer and Hall 2001) such as individuals with a history of problematic substance use.…”
Section: Introductionmentioning
confidence: 99%